2017
DOI: 10.1186/s12891-017-1605-2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical accuracy, function, and quality of life of simultaneous versus staged bilateral Total hip Arthroplasty in patients with Osteonecrosis of the femoral head

Abstract: BackgroundThe optimal surgical option for patients requiring bilateral hip replacement remains controversial. The purpose of this study was to compare surgical accuracy; functional outcome and health-related quality of life; and prosthetic-related complications and revision surgery of a simultaneous bilateral total hip arthroplasty (THA) with those of a staged bilateral THA with an interval between procedures <12 months.MethodsA total of 123 unselected consecutive patients (mean age, 43.3 years) who underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…Osteonecrosis of the femoral head (ONFH) is a devastating disease, which is characterized by cellular demise within the femoral head [1], progressive deterioration of the hip joint [2], and severely lowered quality of life [3, 4]. Although corticosteroid usage [5], alcohol consumption [6, 7], and trauma [8] have been identified as risk factors for ONFH, its pathogenesis remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Osteonecrosis of the femoral head (ONFH) is a devastating disease, which is characterized by cellular demise within the femoral head [1], progressive deterioration of the hip joint [2], and severely lowered quality of life [3, 4]. Although corticosteroid usage [5], alcohol consumption [6, 7], and trauma [8] have been identified as risk factors for ONFH, its pathogenesis remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Despite bilateral knee and hip arthroplasty being frequently performed, most studies paid attention to clinic outcomes, and only a few studies have been published recently on this topic. However, previous studies have not compared costs about THA, to say nothing of comparing costs when pooled both THA and TKA patients [2,7,12]. In this study, we compared the cost of simultaneous and staged procedures among TKA, THA, and their combination groups, found a signi cant difference between the two procedures in three groups.…”
Section: Discussionmentioning
confidence: 86%
“…Kamath et al [1] did not nd signi cant differences for complications between the simultaneous THA group and the staged THA group either. Seung-Chan Kim et al [12] found a lower incidence of postoperative prosthetic-related complications in the simultaneous THA group. When it turns to TKA, several studies reported a lower rate of complications in the simultaneous TKA group [14,16,19,24,25].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations